TRANSFER PRICING IN ROMANIA: GAPS & BEPS IMPACT - Cornelia NASTASE (Business Excellence and Management)
Although transfer prices are a growing topic of discussion in the international literature and tax inspections in Romania are a major debate subject in the tax field, the number of studies approaching these two aspects is reduced. Transfer prices and the practices of eroding the taxable base and profit transfer have an impact on the entire society, from small and medium-sized companies that could be affected by the unfair competition, to the tax administrations that must ensure the fair taxation of profits, multinational companies that must observe arm’s length and should be able to document this fact and up to the citizens of the emerging states. Romanian legislation has gaps that make it difficult for all parties involved in the analysis and documentation of transfer prices and procedures regarding tax inspections requiring modifications for the improvement of the tax obligations’ collection. The effects are major and include tax litigations, additional costs and an impaired collaboration with tax bodies.